Effects of Environmental Heavy Metal Contamination; Human Health and Environmental Toxicology - Aysun Turkmen; Fulya Oztas; Haydar Oztas; Mustafa Turkmen (Chemical and Materials Sciences - Developments and Innovations Vol. 2, 2024)
This study, which investigates the possible environmental effects of heavy metals, shows that most heavy metal products found in nature and resulting from human effects cause various environmental problems and diseases. Heavy metals are characterized by their toxicity to living organisms. Most of them cause environmental and atmospheric pollution and can be fatal to living things. Heavy metals can become highly toxic by mixing with different environmental elements such as water, soil and air, and humans and other living organisms can be exposed to them through the food chain. Pathological research shows that heavy metals cause damage to the brain and peripheral nerves. The increasing use of heavy metals, which have caused some diseases since ancient times, in all kinds of environments due to industrial development, has brought about some health problems. Heavy metal particles can cause edema in the cerebral hemispheres, vascular occlusion, capillary changes in the brain, cerebellar edema with pyknotic, Purkinje cells, and isolated areas of necrosis. It is of great importance to consider the heavy metals found in seafood to reduce the possible effects of heavy metals taken into the food chain because of chronic consumption of fish and other seafood on nerve cells, liver and immune system. Heavy metals could accumulate in living things through their toxicity, longevity in the atmosphere and bioaccumulation. Therefore, contamination of terrestrial and aquatic ecosystems with toxic heavy metals is a significant environmental problem with consequences for public health.